Distribution of vitamin D‐binding protein/group‐specific component gene subtypes in Kuwaiti population - Suhail Najim Al‐Shammri (Molecular Genetics & Genomic Medicine, 2022)
Abstract Background Vitamin D‐binding protein or group‐specific component (Gc) is the major plasma carrier protein of Vitamin D. Two single nucleotide polymorphisms, rs7041 (NM_000583.3:c.1296G>T;NP_000574.2:p.Asp432Glu) and rs4588 (c.1307C>A; p.Thr436Lys), in the GC gene result in three major genotypes, that is, GC1F (c.1296T, c.1307C), GC1S (c.1296G, c.1307C), GC2 (c.1296T, c.1307A), and phenotypes such as Gc1F (p.432Asp, p.436Thr), Gc1S (p.432Glu, p.436Thr), and Gc2 (p.432Asp, p.436Lys). Significant variations in the frequencies of GC subtypes (genotypes/phenotypes) are reported in different populations living in different geographical locations, for example, GC1S/Gc1S (c.1296G, c.1307C/p.432Glu, p.436Thr) and GC2/Gc2 (c.1296T, c.1307A/p.432Asp, p.436Lys) are predominant in Caucasians and people living in the northern hemisphere, and GC1F/Gc1F (c.1296T, c.1307C/p.432Asp, p.436Thr) is predominant in Africans. However, frequencies of major GC subtypes are not known in the Kuwaiti population. In this study, we investigated 512 alleles to identify the major GC subtypes in Kuwaiti nationals. Methods Genomic DNA was isolated from blood samples of 128 healthy subjects. DNA regions covering the targeted mutations were amplified by PCR. Amplified DNAs were sequenced by the Sanger method and analyzed for specific mutations to determine the GC genotypes and phenotypes. Results The results identified the presence of four GC genotypes/phenotypes namely GC1F/Gc1F (c.1296T, c.1307C/p.432Asp, p.436Thr), GC1S/Gc1S (c.1296G, c.1307C/p.432Glu, p.436Thr), GC2/Gc2 (c.1296T, c.1307A/p.432Asp, p.436Lys), and GC3/Gc3 (c.1296G;c.1307A/p.432Glu, p.436Lys). Among the allelic subtypes (n = 512), GC1S (c.1296G; c.1307C) (n = 270, 52.7%) was predominant, followed by GC1F (c.1296T; c.1307C) (n = 138, 27%), GC2 (c.1296T; c.1307A) (n = 72, 14%), and GC3 (c.1296G; c.1307A) (n = 32, 6.3%). Three common subtypes, that is, GC1F (c.1296T; c.1307C), GC1S (c.1296G; c.1307C), and GC2 (c.1296T; c.1307A) are well documented in the literature, but GC3 (c.1296T; c.1307A) is an uncommon variant found in our study subjects. Conclusion We found that GC subtype distribution was unique in the Kuwaiti population, with some affinity to Caucasians. Several factors including ancestral origin, migration history, and environmental forces such as solar intensity may be responsible for the unique distribution of GC subtypes in this population.